Adiponectin downregulation is associated with volume overload-induced myocyte dysfunction in rats - Wang, Li-li (Acta Pharmacol Sin, 2016)
AIM: Adiponectin has been reported to exert protective effects during pathological ventricular remodeling, but the role of adiponectin in volume overload-induced heart failure remains unclear. In this study we investigated the effect of adiponectin on cardiac myocyte contractile dysfunction following volume overload in rats. METHODS: Volume overload was surgically induced in rats by infrarenal aorta-vena cava fistula. The rats were intravenously administered adenoviral adiponectin at 2-, 6- and 9-weeks following fistula. The protein expression of adiponectin, adiponectin receptors (AdipoR1/R2 and T-cadherin) and AMPK activity were measured using Western blot analyses. Isolated ventricular myocytes were prepared at 12 weeks post-fistula to examine the contractile performance of myocytes and intracellular Ca(2+) transient. RESULTS: A-V fistula resulted in significant reductions in serum and myocardial adiponectin levels, myocardial adiponectin receptor (AdipoR1/R2 and T-cadherin) levels, as well as myocardial AMPK activity. Consistent with these changes, the isolated myocytes exhibited significant depression in cell shortening and intracellular Ca(2+) transient. Administration of adenoviral adiponectin significantly increased serum adiponectin levels and prevented myocyte contractile dysfunction in fistula rats. Furthermore, pretreatment of isolated myocytes with recombinant adiponectin (2.5 μg/mL) significantly improved their contractile performance in fistula rats, but had no effects in control or adenoviral adiponectin-administered rats. CONCLUSION: These results demonstrate a positive correlation between adiponectin downregulation and volume overload-induced ventricular remodeling. Adiponectin plays a protective role in volume overload-induced heart failure.